Two Different Views on Monetary Policy Impact: The New Consensus and Post-Keynesian Economics - Marius-Corneliu Marinas (Theoretical and Applied Economics, 2007)

(untitled)
The objective of this study is to make a synthesis of the differences between two new macroeconomic views. A New Consensus has arisen among neoclassical and New-Keynesian economists, such as Romer, Taylor and Walsh. This new view seeks to redefine the application of monetary policy by re-specifying the most appropriate monetary rule, which is used for inflation targeting. The framework of the monetary policy impact requires the usage of a expectations augmented Phillips curve, characterized through the lack of trade-off inflation-unemployment in the long-run. Post-keynesian macroeconomic critical, whose promoters are Arestis, Lavoie and Satterfield, argues that for most of the production levels obtained output change has no effect on inflation. This is a re-formulation of the Keynesian aggregate supply curve, which is entirely horizontal.